Prospects for cordycepin biosynthesis in microbial cell factories - Li, Xiang; Jiang, Rongshuai; Wang, Shenghou; Li, Chenyang; Xu, Yongping; Li, Shuying; Li, Qian; Wang, Liang (Frontiers in Chemical Engineering, 2024)
Cordycepin, an adenosine analog, exhibits diverse bioactivities and holds significant potential for applications in healthcare and agriculture. Fungi of the genus Cordyceps, such as Cordyceps militaris, can naturally produce cordycepin. Current sources of cordycepin primarily involve extraction from fruiting bodies or isolation from liquid fermentation using C. militaris, presenting challenges such as low production intensity, complex separation and purification systems, and high production costs, limiting industrial feasibility. Recent advancements have witnessed the utilization of various fungal chassis cells to successfully engineer heterologous biosynthetic platforms for cordycepin, such as Saccharomyces cerevisiae and unconventional yeasts, offering advantages of high yield, short fermentation cycles, and a broad substrate spectrum. This mini review summarizes the biosynthetic pathways of cordycepin and focused on the comparison of the characteristics, advantages, current performance and prospects for the microbial cell factories, analyzing potential targets for metabolic pathway modification and giving strategies in both genetic engineering and process engineering to enhance production intensity. The mini review particularly emphasizes the crucial role of chassis cell stress tolerance to the toxic product in determining cordycepin yield and highlights the urgent need for high-throughput screening methods for high-yield strains.